Subverting Patriarchal Narratives: Exploring Bhyrappa's Depiction of Sita Through Historiographic Metafiction - S, Anjana; A R, Savitha (The Grove - Working Papers on English Studies, 2023)
The Ramayana, the ancient Hindu epic, has been retold and rewritten in various narrative forms by numerous writers from different countries. It has a global appeal that has inspired authors worldwide to create unique Ramayanas. Among these recreations, Bhyrappa's Uttarakaanda stands out with its multiple story views. This research paper, titled “Subverting Patriarchal Narratives: Exploring Bhyrappa’s Depiction of Sita Through Historiographic Metafiction,” delves into the author's methods of retelling the age-old narrative. The present study utilizes the conceptual frameworks of postmodernism, with a particular emphasis on historiographic metafiction. By delving into the deconstruction of grand narratives and questioning traditional elements that impede women's rights, the article aims to shed light on important thematic concerns. Specifically, the primary focus of this research lies in the analysis of the author's work titled 'Sitayana,' where the narrative spotlight is shifted from Rama to Sita. Through a meticulous examination of the author's adept incorporation of alternative perspectives, the paper explores how this approach resonates with both Indian literature and its readership. Moreover, the article critically engages with the power dynamics that influenced Rama's actions and shaped his understanding of dharma.